The curtain went up, my pants fell down - Winkler, Henry, 1945- (New York, N.Y., U.S.A. : Grosset & Dunlap, 2007)
Failing fifth grade math, Hank must depend on Heather, the class brain, to help him get a "B" on the next test in order for him to be eligible to play the lead in the school play, The King and I.
"World's greatest underachiever"--Cover.
Keywords: Theater -- Juvenile fiction; Schools -- Juvenile fiction; Learning disabilities -- Juvenile fiction; Humorous fiction